Concanavalin-A Induces Granulosa Cell Death and Inhibits Fsh-Mediated Follicular Growth and Ovarian Maturation in Female Rats - Croxatto -Avoni, H (2013)
Reproductive success stems from a finely regulated balance between follicular maturation and atresia, in which the role of carbohydrate structure is poorly understood. Here, we describe for the first time a fraction of purified recombinant human FSH that is capable of bringing about the cell death of granulosa cells and preventing follicular maturation in a rat model. Further analysis by mass spectrometry revealed the presence of the lectin Concanavalin-A (Con-A) within this fraction of recombinant FSH. Using both the fractionated FSH and Con-A, the observed cell death was predominantly located to the granulosa cells. Ex vivo culture of rat follicles demonstrated that follicle degeneration occurred and resulted in the release of a denuded and deteriorated oocyte. Moreover, in vivo experiments confirmed an increase in atresia and a corresponding reduction confined to follicle in early antral stage. As a mechanism of action, Con-A reduces ovarian proliferation, Von Willebrand staining, and angiogenesis. Based on the observation that Con-A may induce granulosa cell death followed by follicle death, our results further demonstrate that follicular carbohydrate moiety is changing under the influence of FSH, which may allow a carbohydrate- binding lectin to increase granulosa cell death. The physiological consequences of circulating lectin-like molecules remain to be determined. However, our results suggest a potential exploitation of carbohydrate binding in fertility and ovarian cancer treatment. This work may shed light on a key role of carbohydrates in the still obscure physiological process of follicular selection and atresia. Copyright © 2013 by The Endocrine Society.